Short Communication: Antibacterial activity of Boesenbergia pandurata, Zingiber zerumbet and Solanum ferox extracts against Aeromonas hydrophila and Pseudomonas sp. - ESTI HANDAYANI HARDI; IRAWAN WIJAYA KUSUMA; WIWIN SUWINARTI; AGUSTINA AGUSTINA; RUDI AGUNG NUGROHO (Smujo International, 2016)
Abstract. Hardi EH, Kusuma IW, Suwinarti W, Agustina, Nugroho RA. 2016. Antibacterial activity of Boesenbergia pandurata, Zingiber zerumbet and Solanum ferox extracts against Aeromonas hydrophila and Pseudomonas sp. Nusantara Bioscience 8:  18-21. This study evaluated the potential antibacterial activity of Boesenbergia pandurata, Zingiber zerumbet and Solanum ferox extracts against Aeromonas hydrophila and Pseudomonas sp. This paper aims to review the best concentration of the extract B. pandurata, Z. zerumbet and S. ferox to inhibit the growth of bacteria A. hydrophila and Pseudomonas sp. on tilapia in vitro test. The concentrations used range from 100-6000 ppm for B. pandurata and S. ferox, meanwhile for Z. zerumbet extracts ranged from 25-1000 ppm. The best concentration was injected to tilapia by intraperitoneal (0.1 mL/fish) to know in vivo inhibition of extract in fish. The results showed that B. pandurata 600 and 900 ppm, and Z. zerumbet 200 and 2000 ppm revealed potent antibacterial activity against A. hydrophila; while the concentration of S. ferox at 400 and 900 ppm inhibits Pseudomonas sp. growth, whereas concentration of 600, 200, and 900 ppm reduced the bacterial pathogen in fish body.